Advances in grid and pervasive computing : 4th International Conference, GPC 2009, Geneva, Switzerland, May 4-8, 2009 : proceedings - GPC; Abdennadher, Nabil; Petcu, Dana (Lecture Notes in Computer Science, 2009)
Grid and Pervasive Computing (GPC) is an annual international conference devoted to the promotion and advancement of all aspects of grid and pervasive computing. The objective of this conference is to provide a forum for researchers and engineers to present their latest research in the ?elds of grid and pervasive computing. Previous editions of the Grid and Pervasive Computing conference were held in: Kunming (China) May 25-28, 2008, Paris (France) May 2-4, 2007, and Taichung (Taiwan) May 3-5, 2006. The fourth edition took place in Geneva, Switzerland during May 4-8, 2009. It was organized by members of the University of Applied Sciences Western Switzerland (Haute Ecole de Paysage, d'Ing' enierie et d'Architecture - hepia), in collaboration with colleagues from various places around the world. The conference spanned a full week, including a three-day technical program where the papers contained in these proceedings were presented. The conf- ence was followed by two tutorial days where attendants had the opportunity to discuss a variety of topics related to the ?elds covered at the conference, at both introductory and advanced levels. The technical program also included an industrial session, with contributions illustrating challenges faced and so- tions devised by industry. Furthermore, the conference o?ered an opportunity for vendors and researchers to present their products and projects at an ex- bition (Grid Village) where solutions supporting the development of grid and pervasive computing were displayed.